2022
DOI: 10.2298/tsci210522311j
|View full text |Cite
|
Sign up to set email alerts
|

Advanced exergy analysis of the natural gas liquid recovery process

Abstract: Energy quality in each country is one of the important indicators of economic development, Which affects the economic growth of that country. Exergy analysis, considering all flow properties including pressure, temperature, composition, is a powerful way to evaluate the energy consumption of equipment such as natural gas and liquefied gas plants. Inefficiency of a system can be defined by the conventional exergy analysis method, While, irreversible resources and real potentials for system imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Additionally, TEP involves the operation of load growth based on demand forecasting [5]. Hence, to implement of reliable energy supply the increase the generation share of wind farms compared to the total generation of electric energy in the traditional systems [6], [7], it is necessary to have a reliable supply of energy in order to maintain customer satisfaction in the power system planning with regard to uncertainties [8], [9]. The research of the power systems considering different areas like power plants, transmission and distribution grids are assessed in this subsection.…”
Section: A Aims and Related Researchmentioning
confidence: 99%
“…Additionally, TEP involves the operation of load growth based on demand forecasting [5]. Hence, to implement of reliable energy supply the increase the generation share of wind farms compared to the total generation of electric energy in the traditional systems [6], [7], it is necessary to have a reliable supply of energy in order to maintain customer satisfaction in the power system planning with regard to uncertainties [8], [9]. The research of the power systems considering different areas like power plants, transmission and distribution grids are assessed in this subsection.…”
Section: A Aims and Related Researchmentioning
confidence: 99%
“…In various industrial systems and processes, exergy analysis locates the exergy destruction and explains the reason for the inefficiency, hence it is important for saving both energy and resources. It focuses on the quality of energy rather than quantity [5]. Exergy analysis of an absorption chiller/KC coupled system has shown that higher exergy efficiency and more electricity production can be achieved in the proposed system [6].…”
Section: Introductionmentioning
confidence: 99%